The Influence of Facebook Social Media Marketing on Brand Awareness On Starlite - Teni Mawarni; Mira Nurfitriya; Tika Annisa Lestari Koeswandi (A Social Science and Entrepreneurship Journal, 2022)
This study aims to determine the influence of Facebook social media marketing on brand awareness. The object of this study is micro, small and medium enterprises (MSMEs) Ornamental Fish Lovers at Starlite in Tasikmalaya City. This study used quantitative calculations by collecting data through the dissemination of questionnaires. The population in this study were followers of the Kamfa Louhan Lovers Tasikmalaya group. The sample in this study was 100 respondents. The result of this study is that facebook social media has a positive and significant effect on brand awareness on Starlite. This is evidenced by a t-test and a one-tailed test which states that the calculated t value is 20.443 ttable 1.66055 with a signif level of 0.000 0.05.